Applying Psychiatry and Psychology Principles to Lifestyle Approaches for Mental and Behavioral Health. Issue 6 (November 2022) - Merlo, Gia; Vela, Alyssa
Research suggests that mental health symptoms and disorders are historically underdiagnosed and undertreated, in part due to the siloed nature of medicine. Yet, approximately 50 million American adults experience a mental health disorder. As the field of lifestyle medicine continues to emerge and grow, there is an important opportunity to address mental health from a lifestyle medicine perspective, as well as to ensure that lifestyle medicine can be utilized for all patients, including those with mental health conditions. To effectively address mental health, the field of lifestyle medicine would benefit from understanding and leveraging the decades of science and practice from the fields of psychiatry and psychology, as well as the expertise of psychiatrists and psychologists who are familiar with the science and trained in lifestyle medicine. Incorporating empirical literature from other areas, utilizing well-established conceptual frameworks, and addressing the overlap between lifestyle medicine and mental health early in, and throughout, training and education, are important steps to move toward addressing mental and behavioral health with a lifestyle medicine approach.